GERAKAN KOIN NU SEBAGAI AKTUALISASI ETIKA SPIRITUAL ISLAM DI TENGAH MASYARAKAT NAHDIYIN - Ahmad, Diki (Program Studi Ekonomi Syariah, 2025)
The KOIN NU movement is a socio-religious phenomenon that reflects the actualization of Islamic spiritual ethics within the life of Nahdliyyin society. This study aims to examine in depth how the KOIN NU movement, initiated by LAZISNU PCNU Garut Regency, represents the spirit of solidarity, simplicity, and communal self-reliance framed within Islamic spiritual values. Using a qualitative-descriptive approach through field studies, interviews, and documentation techniques, the author finds that KOIN NU is not merely a fundraising initiative but a spiritual movement that integrates inner values with tangible action. The findings reveal that the KOIN NU movement functions not only as a means of collecting community donations, but also serves as a moral and spiritual educational platform. The Nahdliyyin community actively participates in regularly allocating a portion of their assets, which indirectly fosters collective awareness and a shared sense of ownership toward a faith-based social movement. Furthermore, this initiative strengthens religious and local cultural identity while reducing dependency on external aid. Thus, KOIN NU can be understood as a praxis of Islamic spiritual ethics that is inclusive and transformative amid the lives of Nahdliyyin society. This study contributes to a broader understanding of Islamic philanthropy dynamics and grassroots movements as strategies for community empowerment based on spiritual values